Characteristics of driver and receiver circuits with a passive transmission line in RSFQ circuits. - Suzuki, H.
We report simulated results of-rapid single flux quantum (SFQ) circuits having driver, receiver, and passive transmission lines for propagating SFQ pulses to investigate the design criteria. We have studied the equivalent input/output resistance of the driver/receiver in various bias conditions and found that the resistance is almost proportional to the bias current of the driver/receiver. Furthermore, we have proposed inserting a series resistor at the end of the superconducting passive transmission line (PTL) for avoiding undesirable flux trapping in the loop and for isolation in regard to the DC current. We also found that the reduction of the bias margin due to the resistance is rather small when the resistance is much smaller than the impedance of the PTL. An operating margin of more than 30% was obtained in the driver/receiver circuits including the PTL and the series resistor
Keywords: RSFQ circuits; Bias current; Driver circuits; Receiver circuits; Series resistor; Superconducting passive transmission line